Dinamika Pasar, Kebijakan Negara, Dan Tuntutan Sosial Dalam Inovasi Pengelolaan Sampah Terpadu (Studi Program Inovasi Sosial “Sadidu” PT Arutmin Indonesia Tambang Satu) - 'Alim, Sarirotul; Meliyanti, Putri Vella; Aisyah, Binti Nur; Mashudi, Mashudi; Ainuddin, Ilham; Kusnandar, Aris (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2025)
Aim – This research aims to understand the role of the Company Performance Rating Program (PROPER) as a reputation-based environmental regulatory instrument and the contribution of social innovation to the sustainability of the coal mining sector. The research focuses on PT Arutmin Indonesia Tambang Satui, with SADIDU social innovation program, as a case study to examine how the company responds to market dynamics, government policies, and social demands. Novelty – The novelty of this research lies in the integration of market dynamics analysis, PROPER instruments, and social innovation. This approach offers a new perspective, as most previous studies have focused solely on regulatory or CSR aspects. Methods – The research employed a qualitative approach with a case study method, supported by data from the Ministry of Environment and Forestry's PROPER report, company documents, and academic literature. Data collection was conducted through interviews, observations, and documentation of the social innovation program for PT Arutmin Indonesia Tambang Satui. The analysis was conducted descriptively and analytically to connect market dynamics, state policies, and social innovation practices. Finding – The research results show that PROPER serves as a state policy instrument for market correction through socio-environmental aspects and addresses the social demands of communities surrounding the mine. PROPER encourages the implementation of social innovation at PT Arutmin Indonesia Tambang Satui. In meeting social demands, the SADIDU program has had a positive impact on increasing alternative incomes for the community and providing renewable energy sources. Limitation and Implication – This research is limited to a single case study, so the results cannot be broadly generalized. However, these findings have important implications for policymakers in strengthening the effectiveness of PROPER, for companies in designing sustainability strategies, and for academics in developing integrative analytical models in the extractive sector.